The Ratio of Linoleic and Linolenic Acid in the Pre-hibernation Diet Influences NFκB Signaling in Garden Dormice During Torpor - Logan, Samantha M.; Watts, Alexander J.; Posautz, Annika; Kübber-Heiss, Anna; Painer, Johanna; Stalder, Gabrielle; Giroud, Sylvain; Storey, Kenneth B. (Frontiers in Molecular Biosciences, 2020)
The fatty acid composition of a pre-hibernation diet can influence the depth and duration of metabolic suppression achieved by hibernators. More specifically, a diet high in n-6 polyunsaturated fatty acids (PUFAs) relative to n-3 PUFAs is essential to maximize torpor expression. However, few studies have investigated how diets with different n-6/n-3 PUFA ratios change stress-inducible cell signaling. Garden dormice (Eliomys quercinus) were fed one of three diets designed with different ratios of n-6 PUFA linoleic acid (LA) and n-3 PUFA linolenic acid (ALA). Then, NFκB signaling was assessed in the white adipose, brown adipose, and liver tissues of euthermic and hibernating dormice via multiplex and RT-qPCR analyses of relative protein and transcript levels, respectively. Dormice fed a high LA diet regulated NFκB signaling in a protective manner in all tissues. NFκB signaling was generally decreased in the high LA group, with significant decreases in the protein levels of NFκB mediators IKKα/β, IκBα, and downstream pro-apoptotic protein FADD. Liver and white adipose from torpid dormice fed a high LA diet increased sod2 expression relative to the other diets or relative to euthermic controls, indicating protection against ROS generated from potentially increased β-oxidation of n-6 PUFAs. The low LA diet increased biomarkers for apoptosis relative to other diets and relative to euthermia, suggesting low LA diets may be detrimental to hibernator health. Overall, this study suggests that changes in the ratio of n-6/n-3 PUFAs in the diet influences apoptotic and antioxidant responses in white adipose, brown adipose, and liver of hibernating garden dormice.